Role of the Retromer Complex in Neurodegenerative Diseases - Li, Chaosi; Shah, Syed Zahid Ali; Zhao, Deming; Yang, Lifeng (Frontiers in Aging Neuroscience, 2016)
Retromer is a protein complex that plays a central role in endosomal trafficking, and retromer dysfunction has been linked to a growing number of neurological disorders. The process of intracellular trafficking and recycling is crucial for maintaining normal intracellular homeostasis, which is partly achieved through retromer complex. The retromer complex plays a primary role in sorting out the cargoes from endosomes back to the cell surface for reuse, to the trans-Golgi network (TGN) or alternatively to specialized endomembrane compartments away from lysosomal-mediated degradation. In most cases, the retromer acts as a core that interacts with associated proteins such as sorting nexin family member 27 (SNX27), the members of the vacuolar protein sorting 10 (VPS10) receptor family, the major endosomal actin polymerization-promoting complex known as wiskott-aldrich syndrome protein and scar homologue (WASH) or other proteins together in sorting the cargoes through various pathways, and some of these cargoes are risk factors for neurodegenerative diseases. Normally, there is a coordinated relationship between these pathways, however, when there is a defect such as haplo-insufficiency or mutation in itself or one or several units of retromer; it will lead to various pathologies.Here, we will summarize the molecular architecture of retromer complex and the roles of this system in intracellular trafficking signaling on pathogenesis of neurodegenerative diseases.